Write as a fraction and simplify. (use the symbol / for your answer)
0.23333...
I

Answers

Answer 1
Answer:

Answer:

23/99

Step-by-step explanation:

0.23 is x.

Because x is recurring in two decimal places, we will multiply it by 100.

100x=23.23

Then we subtract.

100x-x=23.23-0.23

99x=23

x=23/99


Related Questions

How do you write the following standard number in expanded notation?31,606,577 a. 30,000,000 + 1,000,000 + 600,000 + 60,000 + 5,000 + 700 + 7 b. 30,000,000 + 1,000,000 + 60,000 + 600 + 500 + 70 + 7 c. 30,000,000 + 1,000,000 + 600,000 + 6,000 + 500 + 7 + 7 d. 30,000,000 + 1,000,000 + 600,000 + 6,000 + 500 + 70 + 7
What is the domain of the relation? {(−4.5, 0), (−3, 9), (0.9, 0), (4, −7.8), (4, 0), (17, 3)} {0.9, 4, 17} {−7.8, 0, 3, 9} {−4.5, −3, 0.9, 4, 17} {−4.5, −3}
150 has how many 2/7 in it
If t is any real number, prove that 1+(tant)^2=(sect)^2
Help please!!A candle burns down at the rate of 0.5 inches per hour. The original height of the candle was 8 inches.Part A: Write a list of 6 ordered pairs to show the height of the candle in inches (y) as a function of time in hours (x) from the first hour after it started burning. For example, the point (0, 8) would represent a height of 8 inches after 0 hours. Explain how you obtained the ordered pairs. (5 points)Part B: Is this relation a function? Justify your answer using the list of ordered pairs you created in Part A. (2 points)Part C: If the rate at which the candle burned was 0.4 inches per hour instead of 0.5 inches per hour, would the relation be a function? Explain your answer using input and output values. (3 points)

How do I find w using this table?

Answers

try mixing the numbers and put it in order. you can figure out what w represents as u find the missing number

Which products result in a perfect square trinomial? Check all that apply.A=(–x + 9)(–x – 9)
B=(xy + x)(xy + x)
C=(2x – 3)(–3 + 2x)
D=(16 – x2)(x2 – 16)
E=(4y2 + 25)(25 + 4y2)

Answers

The correct answers are:

B=(xy + x)(xy + x) ; C=(2x – 3)(–3 + 2x) ; and E=(4y² + 25)(25 + 4y²)

Explanation:

In order to have a perfect square trinomial, we must multiply two binomials that are exactly the same.  For (xy+x)(xy+x), are multiplying two identical binomials.

For (2x-3)(-3+2x), we are multiplying two binomials that are the same but written in a different order.  The same is true of (4y² + 25)(25 + 4y²).

Answer:

A and E and C

Step-by-step explanation:

A perfect square trinomial can be written as the square of a binomial.

If f(x) = 3x + 2 and g(x) = x2 + 1, which expression is equivalent to (f * g) (x)

Answers

 f(x) = 3x + 2 and g(x) = x² + 1
⇒(f * g) (x) = ( 3x + 2 ) × ( x² + 1 ) 
                  = 3x³ + 2x² + 3x +2

Use a trigonometric ratio to find the value of x. round your answer to nearest tenth

Answers

x = base / tan(angle)

x = 9 / tan(20)

x = 24.73

rounded to nearest tenth x = 24.7

The value of x = 24.7

What is tangent angle?

For a right triangle, a tangent angle is,  tan\theta=(opposite ~ side)/(adjecent ~ side)

For given example,

Consider tan(20°)

Using the formula of tangent angle,

tan(20)=(9)/(x)

0.364=(9)/(x)

⇒ x = 9/0.364

x = 24.7

Therefore, the value of x = 24.7

Learn more about tangent angle here:

brainly.com/question/19486069

#SPJ2

If x^5y^4z^2 <0 , which of the following must be true?I xy <0
II yz <0
III xz <0

Answers

x^5y^4z^2 < 0\n\ny^4\geq0\ for\ y\in\mathbb{R}\n\nz^2\geq0\ for\ y\in\mathbb{R}\n\nx^5 > 0\ for\ y\in\mathbb{R^+}\ and\ x^5 < 0\ for\ x\in\mathbb{R^-}\n\n------------------------------\n\nx^5\underbrace{y^4z^2}_(> 0) < 0\iff x^5 < 0\Rightarrow xy < 0\ \wedge\ xz < 0\n\n------------------------------\n\nAnswer:I\ xy < 0\ and\ III\ xz < 0.

Find the mindpoint of ab a(-3,7) and b(-7,-6)

Answers

Answer:

Step-by-step explanation:

The midpoint of AB is (-5,1), if A(-3,8) and B(-7,-6). How to find out the midpoint of coordinates?The midpoint of coordinates is found by measuring the distance between two endpoints and dividing the obtained result by 2. Apart from this, one more method is there which is to add the two X-coordinates of the endpoints and divide them by 2. The same concept is applied to the Y-coordinates as well. According to the question, A = (-3,8) and B = (-7,-6). The formula is as follows:M(x,y) = ((x₁+x₂)/2 , (y₁+y₂)/2). Putting the above values in the mentioned formula, we get:M(x,y) = ((-3-7)/2 , (8-6)/2).

M(x,y) = (-5 , 1). Therefore, the midpoint of AB is (-5,1), if A(-3,8) and B(-7,-6).To learn more about the Midpoint of coordinates, refer to the link: brainly.com/question/28308761